2022
DOI: 10.1093/jn/nxab400
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Glycopeptidomics Reveals Intact Glycomacropeptide Is Digested to a Wide Array of Peptides in Human Jejunum

Abstract: Background Bovine milk κ-casein-derived caseinomacropeptide (CMP) is produced in large quantities during cheesemaking and has various biological activities demonstrated via in vitro and in vivo experiments. Previous studies examined protein degradation and peptide release after casein or whey protein consumption. However, whether purified intact CMP which is partially glycosylated survives intact to its presumed site of bioactivity within the gut remains unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…While the beneficial effects of GMP do not seem to involve mechanisms driven by the gut microbiota, we hypothesize that the peptide’s actions stem from direct interaction with various receptors within the gut or post-absorption. Although previous studies have suggested that GMP is predominantly found in circulation, recent research has revealed that a significant portion of GMP is degraded into smaller peptides of 11 to 20 amino acids within 1 to 3 h post-consumption [ 76 ]. This finding raises the possibility that the peptide’s effects may be primarily mediated by its interaction with various receptors directly within the gut rather than following absorption into circulation.…”
Section: Discussionmentioning
confidence: 99%
“…While the beneficial effects of GMP do not seem to involve mechanisms driven by the gut microbiota, we hypothesize that the peptide’s actions stem from direct interaction with various receptors within the gut or post-absorption. Although previous studies have suggested that GMP is predominantly found in circulation, recent research has revealed that a significant portion of GMP is degraded into smaller peptides of 11 to 20 amino acids within 1 to 3 h post-consumption [ 76 ]. This finding raises the possibility that the peptide’s effects may be primarily mediated by its interaction with various receptors directly within the gut rather than following absorption into circulation.…”
Section: Discussionmentioning
confidence: 99%
“…When fed, GMP undergoes digestion within the gastrointestinal tract. Koh et al [26] demonstrated that GMP is broken down into many peptide fragments during human digestion, including many that are known bioactive peptides. We observed that in vitro-digested GMP strongly inhibited production of both TNF-α and IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…Peptides that are released from WPI and GMP during gastrointestinal digestion in the consumer would have the potential to affect immunoregulation by interacting with intestinal epithelial and immune cells. Koh et al [26] demonstrated that during human consumption, GMP is digested into smaller peptides, many of which share homology with known bioactive peptides. The digestion-released GMP-derived fragments thus have a higher likelihood of being able to exert immunomodulatory effects within the human gut than the intact form of GMP.…”
Section: Introductionmentioning
confidence: 99%
“…More research is needed to determine the effects of GMP supplementation on the microbiome of IBS patients. Since GMP is known to be digested partially within the human gut [ 113 , 114 , 115 ], encapsulation and other delivery strategies may be needed to enhance its effectiveness.…”
Section: Gmp and The Microbiome In Ibsmentioning
confidence: 99%